Supersoft X-ray sources as transient phases of cataclysmic variable evolution - Webbink, R (2001)
Cataclysmic binaries first reaching mass transfer with marginally stable mass ratios can achieve mass transfer rates high enough to sustain stable hydrogen burning and become supersoft X-ray sources. Such systems are concentrated in orbital period just above the period gap, and can, in the most favorable circumstances, achieve X-ray lifetimes in excess of 3 x 10(5) yr. They have white dwarfs of moderate mass (0.7 - 0.9 M.), and may therefore tend to lower X-ray temperatures and luminosities than the more populous, longer-period supersoft sources with donor masses exceeding similar to 1.5 M.. Their properties offer a direct probe of orbital angular momentum loss rates.